Tofu Wastewater Treatment Planning with Anaerobic Baffled Reactor (ABR) and Activated Sludge Application - Naomi Aurora Margareth Br. Simanjuntak; Nurulbaiti Listyendah Zahra; I Wayan Koko Suryawan (Universitas Hasanuddin, 2021)
Wastewater from tofu industry produces water with high organic content. Organic pollutant pollution from tofu industry has an impact potential on receiving water bodies. The purpose of the study is to understand the characteristics of the wastewater and conducting the study design of the wastewater treatment plant (WWTP) in the tofu industry. Characterization of tofu industrial wastewater was carried out based on BOD5, COD, TSS, and pH parameters. Sampling was carried out in the tofu-making industrial area of South Sukabumi Village. The organic content in the form of BOD5 and COD respectively is 2843.5 m/L and 7743.5 mg/L. Thus, the aerobic process could not be applied directly as requiring very high oxygen supply. BOD5, COD, TSS, and pH parameters in the industry do not meet Minister of Environment Regulation Number 05 Year 2014 Concerning Wastewater Materials Quality. The units needed in the planning are a collection well, neutralization tank, abr, activated sludge, and final settling tank. Land area needed in the planning of the units is 8.89 m2. The effluent of wastewater which expected to have a neutral pH and the concentration for each BOD5, COD, TSS parameter reaches 24.69 mg/L; 63.32 mg/L; 26.7 mg/L. The total cost of the required WWTP design is Rp 187,977,000.00.